Force Production of Diverse Populations - Sanderson, Macy (My University, 2024)
This study examines how physical activity levels influence hand grip strength and accuracy. Sixteen participants split into active and inactive groups (both male and female), completed tests to measure their maximum grip strength and their ability to reproduce submaximal forces (50% and 35% of their maximum). The findings revealed that active individuals consistently demonstrated stronger grip strength, better coordination between hands, and greater accuracy in hitting target force levels. In contrast, inactive participants showed weaker grip strength, larger imbalances between hands, and less precise control during submaximal tasks. These differences highlight how regular physical activity supports better muscle balance, coordination, and motor precision. Active males showed more symmetrical hand strength, while active females outperformed their inactive peers in overall grip strength. Meanwhile, inactive participants struggled with accuracy and consistency, reflecting the impact of a sedentary lifestyle on motor skills. This study highlights the importance of staying active—not just for physical strength but also for improving everyday functional abilities. These insights could inform exercise programs and rehabilitation strategies, helping people of all backgrounds stay independent and thrive.
Keywords: Physical activity; hand grip strength; force accuracy